Can Medicare Be Saved? Reflections from Alberta - Robert Bear (HealthcarePapers, 2000)
Most Canadians would consider the very question of saving medicare as a threatening prospect. Even more threatening should be the growing consensus that the above question is no longer relevant, that medicare in its current form cannot be saved and that the debate must turn to how our healthcare system should evolve in order to remain sustainable.